DISTRIBUSI PENDAPATAN ANTAR DAERAH DI PROVINSI SULAWESI UTARA - Bella Fitria Laloan; Gene H. M. Kapantow; Oktavianus ., Porajouw (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the distribution of income among regions in North Sulawesi Province. This research was conducted for 4 months from October 2017 until February 2018 in North Sulawesi Province. In this study the data used were secondary data obtained from the Central Bureau of Statistics (BPS) of North Sulawesi Province. The data was processed using Gini Index analysis method (calculated BPS data) and Williamson Index and presented in tabular form. The results of the research showed that the level of the uniformity of the income distribution among regions in North Sulawesi tended increase as incated by the value of Williamson Index which raised from 0,475 in 2012 to 0,543 in 2016. While the income distribution in North Sulawesi was relative even indicated by the value of Gini Index in 2012 0.43 dropped 0,39 in 2016.